Spatial and temporal distribution characteristics and prediction analysis of nitrogen and phosphorus surface source pollution in Shandong Province under the climate and land use changes - Li, Qingsong; Zhang, Jincai; Zhang, Jiawen; Gao, Huishan; Chen, Weiqiang; Huang, Junchang; Guo, Yulong; Yue, Shuaijun; Li, Genming (Frontiers in Ecology and Evolution, 2023)
To explore the characteristics of non-point source pollution of nitrogen (N) and phosphorus (P) under the background of climate and land use in Shandong Province. First, use InVEST NDR module in the model, in 2010 and 2020 in Shandong province of N and P non-point source pollution were simulated; Then, based on precipitation data under three different global climate models (MRI-ESM-0, GFDL-ESM4, Ec-Earth3) and two Shared Socioeconomic Pathways (SSP245, SSP585), and land use data under two Shared Socioeconomic Pathways (SSP245,SSP585),to simulate and predict the non-point source pollution of N and P in Shandong Province in 2030.The results showed that: (1) On the time scale, the output load and total output of N and P decreased during 2010-2020, while the output load and total output of N and P increased during 2020-2030. (2) On the spatial scale, the spatial distribution of N and P output loads in 2010, 2020 and 2030 is roughly the same, showing the characteristics of "low in the northwest and high in the southeast". (3) Different climate scenarios have great influence on N and P output load and total output, and the N and P pollution in SSP585 scenario is more serious. The total output of N and P did not change much in different climate models, while the spatial distribution of the output load of N and P varied significantly, indicating that different climate models had a greater impact on the spatial distribution of the output load of N and P. (4) The overall cold hot spot pattern of nitrogen and phosphorus pollution in Shandong Province is stable, basically showing a "band + cluster + scatter" distribution pattern, and the hot spot area in the central and southern region of Shandong Province changes little regardless of the model, and the northwest is basically a cold spot area, and the nitrogen and phosphorus hot spot area under the SSP245 scenario in Ec-Earth3 model is the least. e.